Understanding farmers perception on adoption of drip irrigation in Semjong Gewog, Tsirang Dzongkhag - Sangay Lhamo (CNR, Lobesa Sangay Lhamo, 2022)
includes acknowledgement and abstract
Keywords: Thesis